Integrating the Islamic concept of hikmah and positive psychology for holistic well-being: A literature review - Diponegoro, Ahmad Muhammad; Septiasih, Antonia Dian; Hanifah, Hanifah; Ayuningrum, Olivia; Suryani, Suci Fajar; Nengsih, Tri Widya; Khasanah , Fachrun Nisa Sofiyah (Universitas Ahmad Dahlan, 2025)
In the face of increasingly complex challenges in modern life, there is a pressing need to integrate Islamic wisdom (hikmah) with the principles of positive psychology to achieve holistic well-being. Wisdom, as the capacity to comprehend and apply knowledge meaningfully, is deeply rooted in Islamic teachings. Concurrently, positive psychology emphasizes the cultivation of individual strengths and potential to promote psychological flourishing. This study aims to explore the intersections between hikmah as derived from the Qur’an and Hadith and the foundational tenets of positive psychology in promoting mental health, resilience, and life satisfaction as components of holistic well-being. A qualitative literature review was conducted using a meta-ethnographic synthesis approach. This method facilitates the integration of findings from multiple qualitative studies to generate new theoretical insights into a specific phenomenon. It is particularly suitable for research that investigates subjective experiences, perceptions, and behaviors in depth, with the potential to inform both theoretical development and practical applications. The literature search was conducted through major academic databases, including Google Scholar, SpringerLink, PubMed, and Cambridge University Press. Search terms included “wisdom,” “Islam,” “positive psychology,” and “well-being.” Inclusion criteria encompassed peer-reviewed articles published between 2020 and 2024 in either English or Indonesian. A total of eight relevant articles were selected for synthesis. The findings highlight a strong association between religiosity and social support with wisdom. Wisdom, in turn, exerts a positive influence on psychological well-being. Furthermore, religiosity and social support contribute indirectly to psychological well-being through the mediating role of wisdom. Positive psychology interventions were found to enhance wisdom, resilience, and cognitive flexibility. Additionally, spiritual and health-promoting behaviors were positively correlated with psychological well-being, with health-related behaviors serving as mediators. Wisdom was identified as a significant predictor of subjective well-being, particularly in later life stages. While spirituality supports mental health, its contribution to wisdom appears to be less pronounced compared to prosocial behavior and self-regulation. Interventions rooted in Islamic values have shown potential in improving psychological well-being, and multicomponent positive psychology programs have demonstrated efficacy in both enhancing well-being and alleviating depressive symptoms. Overall, wisdom and religiosity are positively associated with subjective well-being, with mastery and life purpose serving as mediating variables.